Needs Analysis in ESP as a Motivator and Means to Optimise Academic ESP Courses - Stefanova, Albena; Bozeva, Denitsa (English Studies at NBU, 2023)
The paper presents the results of a needs analysis conducted to optimise the academic ESP courses at a Bulgarian university. There are few studies on the issue in Bulgaria unlike the global situation with universities and employers studying the ESP needs of their students and workforce regularly. Hence by carrying out a survey of the students at this particular university along with students from another six local universities and fifteen universities from eleven countries worldwide, all with the same profile, the research team expected to gather reliable information about the course parameters that require improvement. The student sample includes 939 local and 167 foreign students. In addition, a survey of 32 local faculty teaching language and/or subject matter was conducted to triangulate data and strengthen the research contribution to the enhanced course effectiveness based on the greater motivation for ESP acquisition by formulating recommendations for syllabi development.